Implementasi Program Pencegahan Perkawinan Usia Anak di Kabupaten Lombok Barat - Kartiwa Karpi, Iwa; Sumaryana, Asep; Buchari , Achmad (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2024)
This study explains the implementation of the Gamak program in West Lombok Regency, which has succeeded in reducing the number of child marriages in the 2019-2022 period. This success is a contradiction amidst the increasing proportion of child marriages in the West Nusa Tenggara region and the COVID-19 pandemic, which should increase the risk of child marriage. The aim of the research is to determine the implementation process of the Gamak program which is carried out interorganizationally through implementing units at the district, sub-district, and village levels. The implementation approach uses the Van Meter & Van Horn (1975) - Model of the Policy Implementation Process. The research results show that the Gamak has been supported by aims, targets, instruments, and implementing units which are fully defined in West Lombok Regent Regulation Number 30 of 2018 and the Technical Instructions for Gamak. In its implementation, procedural adjustments occur to increase the effectiveness of program implementation.